The effect of human capital on CO2 emissions: Macro evidence from China - Yao, Yao; Zhang, Lin; Salim, Ruhul; Rafiq, Shuddhaswatta (2020)
We study the effect of human capital on CO2 emissions using the Chinese provincial panel over the period 1997–2016. Allowing for cross-sectional dependence and structural breaks, we find a negative association between human capital and CO2 emissions in the long run and attribute it to the influences from younger workers and workers with advanced human capital. In particular, our results suggest that a one-year increase in average schooling reduces CO2 emissions by 12 per cent. Using disaggregated emission dataset by energy sources and end emitters, we demonstrate this negative association is likely to manifest through technology effect and the improvement in energy efficiency. These manifestations are limited to production sector. Our finding suggests a promising avenue for abating greenhouse gases without impeding economic growth.